Propagation phenological phase and fruiting habits of the Nitraria tangutorum in the lower reaches of Shiyang River - LIU Hujun; LIU Yun; LIU Shujuan; ZHAO Peng; QI Fujun; LIU Kailin (Xibei zhiwu xuebao)
[Objective] Fruiting habits was the basis for the selection of plant varieties and scientific management, and the investigation of Nitraria tangutorum in the lower reaches of Shiyang River determined the propagation phenological phase and characteristics of fruit branches, fruit traits, providing a reference for excellent germplasm selection and cultivation management. [Methods] Combined with the biological and ecology survey method, the phenological and biological analysis methods were used to statistically analyze the phenology and fruit habits by the basis of the field investigation in the survey area. [Results] 3- year-old N . tangutorum began to flower and bear fruit. The flower buds differentiation in the same year, and the mixed bud would develop a fruit branch in the second year, and flowers and bears fruit. Both of vegetative branches and branches thorn could generate flower buds, of which 66.67% were vegetative branches. It was results that the mother branch grew fruit branches, vegetative branches, fruiting branches + vegetative branches and branches thorn, and the fruiting branches were significantly more than other types of branches (P <0.05). The average number of fruiting branches accounted for 81.49%. The fruit branches could be divided into short fruit branches (2-6 cm, 42.72%), medium fruit branches (6-10 cm, 52.43%) and long fruit branches (10.1-11.6 cm, 4.85%). The average number of infructescence of vegetative branches and branches thorn was 6.62 and 6.69, respectively and the fruit rate was respectively 56.41% and 39.13% of the 3 fruits, while the difference between the different inflorescences was not significant (P >0.05). The fruit shape of N . tangutorum was oblong, and the relationship between the transverse diameter and its traits was greater than the longitudinal diameter, and it significantly affected the weight of the fresh fruit. The period from flower bud to fruit dropping of N . tangutorum was about 25-40 d, which flowering and fruit stage with the climate warm of the trend of advance and prolongation. The fruit traits would be affected by the environment. [Conclusion] The flowering and fruiting stages of N . tangutorum tended to advance and lengthen with climate warming, and the fruiting mother branch was a composite branch, and the branch type and fruiting were less affected by the habitat than that of fruit index.